The logical status of the biblical book of Titus - Onkware, Kennedy; Iteyo, Crispinous; Obwoge, Hezekiah (My University, 2017)
The purpose of this article is to determine the logical status of the Biblical Book of Titus. It does this by exploring the philosophical problem of the definition of truth and how it is to be applied. It delves into St. Paul’s usage of philosophy in the Epistle of Titus. A careful examination of the book reveals that there are apparent logical contradictions in St. Paul’s usage of “truth”. It is argued and concluded that the book of Titus is a classic example of very few philosophical treatises which can be easily shown to be dead and maybe raising questions of its religious value.
Keywords: Lies; Logic; Truth